Adhesive body using thermoplastic adhesive film
A resin composition with acid-modified polyethylene and elastomer ensures strong and flexible bonding of UHMWPE, addressing adhesion and durability issues in low-temperature environments.
Patent Information
- Application Number
- JP2023175779
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-10-11
- Publication Date
- 2025-04-23
- Estimated Expiration
- 2043-10-11
AI Technical Summary
Existing methods for bonding ultra-high molecular weight polyethylene (UHMWPE) are limited by poor adhesion, especially in low-temperature environments, and result in crevice corrosion and durability issues when used with materials having different thermal expansion coefficients.
A resin composition comprising acid-modified polyethylene and a polyethylene-based elastomer, with a thermoplastic adhesive film containing 5 to 95% of each component, which is used to bond UHMWPE with other materials, ensuring flexibility and adhesion even at low temperatures.
The adhesive structure provides excellent adhesion strength, flexibility, and resistance to deformation, allowing UHMWPE to be used in applications where previous methods fail, particularly in low-temperature conditions.
Smart Images

Figure 2025066294000001 
Figure 2025066294000002
Abstract
Description
[Technical field]
[0001] The present invention relates to an adhesive body using a thermoplastic adhesive film. [Background technology]
[0002] Ultra-high molecular weight polyethylene has excellent lubricity, abrasion resistance, impact resistance, and low temperature resistance, and is used in sliding parts, etc., but since it is a poorly adhesive material, it is difficult to fix it with an adhesive. Chemical methods have been proposed as a method for bonding ultra-high molecular weight polyethylene. For example, Patent Document 1 proposes a method for bonding ultra-high molecular weight polyethylene in which a monomer selected from acrylic acid, methacrylic acid, and dialkylaminoalkyl (meth)acrylate is photo-graft polymerized onto the surface of the ultra-high molecular weight polyethylene to modify the surface, and then the ultra-high molecular weight polyethylene is bonded with a vinyl-based adhesive. Furthermore, as a method for fixing ultra-high molecular weight polyethylene, Patent Document 2 proposes a method in which a first sheet made of ultra-high molecular weight polyethylene, a core material having a plurality of through holes formed therethrough in the thickness direction, and a second sheet made of a synthetic resin that can be welded to the ultra-high molecular weight polyethylene are stacked together, and the first and second sheets are welded together via the through holes to integrate them with the core material. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2007-153945 A [Patent Document 2] JP 2015-047723 A Summary of the Invention [Problem to be solved by the invention]
[0004] The chemical method described in Patent Document 1 and the like is limited to only a limited number of businesses that can carry out chemical treatment, and the adhesives that can be used are also limited, making it difficult to apply the method to a wide variety of applications. In the method described in Patent Document 2, although the core material and the ultra-high molecular weight polyethylene are integrated, they are sandwiched between the front and back, and it is difficult to apply the method to, for example, a thick core material. In addition, since the obtained laminate is covered on both sides with polyethylene, which makes adhesion difficult, it is necessary to provide mounting holes in the core material and fix it with bolts or the like (see 0015, FIG. 3, etc. of Patent Document 2). However, since ultra-high molecular weight polyethylene has a low rigidity and a high linear expansion coefficient compared to metals, etc., gaps are likely to occur between the core material and the fixed member due to dimensional changes and distortion during bolt fixation, and when these are metals, there is a problem that crevice corrosion occurs.
[0005] This crevice corrosion can be prevented by using hot melt adhesives for bonding, but hot melt adhesives have durability issues and, in particular, have poor adhesive properties at low temperatures, so they could not be used to bond ultra-high molecular weight polyethylene components, which are often used in harsh environments. An object of the present invention is to provide an ultra-high molecular weight polyethylene bonded body having excellent adhesiveness in a low-temperature environment. [Means for solving the problem]
[0006] The means for solving the problems of the present invention are as follows. 1. A resin composition comprising (A) an acid-modified polyethylene and (C) a polyethylene-based elastomer, an adherend is adhered to both sides of a thermoplastic adhesive film containing 5 to 95% by weight of the (A) and 5 to 95% by weight of the (C) relative to the entire resin composition; An adhesive structure, characterized in that at least one of the adherends is ultra-high molecular weight polyethylene. 2. The thermoplastic adhesive film contains (B) linear low-density polyethylene, 2. The adhesive body according to 1, wherein the resin composition contains 40% by weight or less of (B) based on the entire resin composition. 3. The tensile modulus of the thermoplastic adhesive film is 50 MPa or more and 950 MPa or less, 3. The adhesive structure according to 1 or 2, characterized in that the film thickness is 10 μm or more and 500 μm or less. 4. The bonded structure according to any one of 1. to 3., characterized in that the −30° C. impact strength measured by the following method is 2 J or more. (Method of measuring impact strength at -30℃) With reference to JIS K6854-3, a thermoplastic adhesive film (0.08mm thick x 12.5mm wide x 10mm long) was layered between an aluminum plate (0.5mm thick x 12.5mm wide x 130mm long) and an ultra-high molecular weight polyethylene plate (0.5mm thick x 12.5mm wide x 130mm long), arranged at a length of 10mm to form a three-layer structure, and the plates were hot-pressed and bonded at 0.5MPa for 60 seconds using a hot plate press (CYPT-50, manufactured by Shinto Kogyo) set at 180°C on the aluminum plate side and 70°C on the ultra-high molecular weight polyethylene side to obtain an adhesive sample. The non-bonded ends of the upper and lower adherends were bent 90 degrees to form a T-shape, and each end was fixed so that the bonded portion was in the center of the test piece clamp of a film impact tester (TM-701-200, manufactured by Tester Sangyo), and left to stand for 5 minutes in an environment of -30°C. After that, an impact was applied to the ultra-high molecular weight polyethylene surface near the bonded surface by free-fall using a pendulum with a 1 / 2 inch ball at the tip, and the strength was measured when the bonded portion broke or the interface peeled off at the bonded portion, and the -30°C impact strength (J) was obtained. 5. The adhesive structure according to any one of 1. to 4., characterized in that the peel adhesion strength measured by the following method is 40 N / 25 mm or more. (Method of measuring peel strength) With reference to JIS K6854-3, a thermoplastic adhesive film (0.08 mm thick x 25 mm wide x 100 mm long) was layered between an aluminum plate (0.5 mm thick x 25 mm wide x 130 mm long) and an ultra-high molecular weight polyethylene plate (0.5 mm thick x 25 mm wide x 130 mm long), arranged at a length of 100 mm to form a three-layer structure. A hot plate press (CYPT-50, manufactured by Shinto Kogyo) was used with the aluminum plate side set to 180°C and the ultra-high molecular weight polyethylene side set to 70°C to perform hot press bonding at 0.6 MPa for 60 seconds to obtain an adhesive sample. The non-bonded ends of the upper and lower adherends were bent 90 degrees to form a T-shape, and the ends were gripped with a jig up to 20 mm from the T-shape. The lower adherend was fixed, and the jig gripping the upper adherend was pulled upward at a tensile speed of 100 mm / min. The strength when the bonded area broke or the interface peeled off at the bonded area was measured with an autograph (Shimadzu Corporation AGS-X) to obtain the peel adhesion strength (N / 25 mm). 6. The adhesive structure according to any one of 1. to 5., characterized in that the tensile shear adhesive strength measured by the following method is 5 MPa or more. (Method of measuring tensile shear adhesive strength) With reference to JIS K6850, a thermoplastic adhesive film (0.08 mm thick x 20 mm wide x 10 mm long) was layered between an iron plate (0.8 mm thick x 20 mm wide x 75 mm long) and an ultra-high molecular weight polyethylene plate (5 mm thick x 20 mm wide x 75 mm long), arranged at a length of 10 mm to form a three-layer structure. This was then hot-pressed and bonded at 0.5 MPa for 60 seconds using a hot plate press (Shinto Kogyo Co., Ltd. CYPT-50) set at 180°C on the iron plate side and 70°C on the ultra-high molecular weight polyethylene side to obtain an adhesive sample. The non-bonded ends of the upper and lower adherends were gripped with a jig up to a point 50 mm from the end. The lower adherend was fixed, and the jig gripping the upper adherend was pulled upward at a tensile speed of 100 mm / min. The strength when the bonded area broke or the interface peeled off at the bonded area was measured with an autograph (Shimadzu Corporation AGS-X), and the tensile shear adhesive strength (MPa) was obtained by dividing this by the bonded area. 7. The adhesive body according to any one of 1. to 6., wherein the other adherend is a metal. Effect of the Invention
[0007] The adhesive of the present invention has excellent adhesive strength even at low temperatures, and can be used in applications where it may be exposed to low-temperature environments. The adhesive of the present invention uses ultra-high molecular weight polyethylene (UHMWPE), which is a difficult-to-adhere material, as one of the adherends, and can expand the application of UHMWPE to applications where it could not be used before. The thermoplastic adhesive film used in the bonded body of the present invention contains an elastomer component (C), so it can maintain flexibility in a low-temperature environment, can relieve distortion, and is unlikely to warp or peel after bonding, even if there is a large difference in the thermal expansion coefficients of the adherends, so it can bond UHMWPE and metals. In addition, since the thermoplastic adhesive film itself is flexible, it can follow the shape of the adherend after bonding, and can prevent deformation and peeling after bonding. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0008] ·Adhesive body The adhesive of the present invention comprises a resin composition containing (A) an acid-modified polyethylene and (C) a polyethylene-based elastomer, The thermoplastic adhesive film contains 5 to 95% by weight of (A) and 5 to 95% by weight of (C) based on the entire resin composition, and an adherend is adhered to both sides of the film. At least one of the adherends is ultra-high molecular weight polyethylene. In this specification, the expression "a to b" (a and b are numerical values) means a numerical range of not less than a and not more than b.
[0009] Thermoplastic adhesive film The thermoplastic adhesive film (resin composition) used in the present invention is made of a resin composition containing (A) an acid-modified polyethylene and (C) a polyethylene-based elastomer, The resin composition contains 5 to 95% by weight of (A) and 5 to 95% by weight of (C) based on the total weight of the resin composition. In addition, the resin composition may contain linear low-density polyethylene (B) as an optional component. Furthermore, the resin composition of the present invention may contain other components in addition to the components (A) to (C).
[0010] (A) Acid-modified polyethylene Acid-modified polyethylene is a polyethylene resin that has been acid-modified by grafting an unsaturated carboxylic acid or an unsaturated carboxylic acid derivative. By containing acid-modified polyethylene, it exerts adhesion to the adherend. On the other hand, if the density of a thermoplastic adhesive film is too high, it becomes too hard in a low-temperature environment, and if the density of a thermoplastic adhesive film is too low, the adhesive layer becomes soft, which may reduce the adhesive strength or reduce the blocking resistance.
[0011] There are no particular limitations on the polyethylene used for the acid-modified polyethylene, and any of the following can be used: high-density polyethylene (HDPE), in which the polymerized ethylene chains have almost no branching and which has excellent tensile strength and chemical resistance; low-density polyethylene (LDPE), which has long side chains branched from the ethylene chain; linear low-density polyethylene (LLDPE), which is produced by polymerizing ethylene and 1-butene or 1-hexene in the presence of a Ziegler-Natta catalyst; and metallocene-catalyzed linear low-density polyethylene (mLLDPE), which is produced in the presence of a metallocene catalyst.
[0012] Examples of unsaturated carboxylic acids for acid modification include maleic acid, itaconic acid, fumaric acid, acrylic acid, and methacrylic acid. Examples of derivatives of the unsaturated carboxylic acids include maleic acid monoesters, maleic acid diesters, maleic anhydride, itaconic acid monoesters, itaconic acid diesters, itaconic anhydride, fumaric acid monoesters, fumaric acid diesters, fumaric anhydride, alkyl acrylates such as methyl acrylate, and alkyl methacrylates such as methyl methacrylate. Among these, maleic anhydride is preferred from the viewpoint of adhesion. As the unsaturated carboxylic acid, one or more of these can be used in combination. The amount of acid modification of the acid-modified polyethylene (the amount of structural units derived from the grafted unsaturated carboxylic acid or unsaturated carboxylic acid derivative) depends on the type of the grafted unsaturated carboxylic acid or unsaturated carboxylic acid derivative, but in the case of maleic anhydride, for example, from the viewpoint of adhesiveness, it is preferably 0.01% by weight or more, more preferably 0.1% by weight or more, whereas from the viewpoint of film formability, it is preferably 10.0% by weight or less, more preferably 5.0% by weight or less.
[0013] The method for obtaining the acid-modified polyethylene is not limited, and for example, a method can be used in which a resin composition containing 100 parts by weight of a polyethylene resin, 0.01 to 5 parts by weight of an unsaturated carboxylic acid and / or an unsaturated carboxylic acid derivative, and 0.01 to 5 parts by weight of an organic peroxide is melt-kneaded to graft the unsaturated carboxylic acid and / or an unsaturated carboxylic acid derivative onto the high-density polyethylene resin.
[0014] Examples of organic peroxides include dicumyl peroxide, di-tert-butyl peroxide, 2,5-dimethyl-2,5-di-(tert-butylperoxy)hexane, 2,5-dimethyl-2,5-di(tert-butylperoxy)hexyne-3, 1,3-bis(tert-butylperoxyisopropyl)benzene, 1,1-bis(tert-butylperoxy)-3,3,5-trimethylcyclohexane, n-butyl-4,4-bis(tert-butylperoxy)valerate, benzoyl peroxide, p-chlorobenzoyl peroxide, 2,4-dichlorobenzoyl peroxide, tert-butyl peroxybenzoate, tert-butylperoxyisopropyl carbonate, diacetyl peroxide, lauroyl peroxide, and tert-butylcumyl peroxide. These can be used alone or in combination of two or more. Among these, from the viewpoint of adhesiveness, 2,5-dimethyl-2,5-di-(tert-butylperoxy)hexane and 2,5-dimethyl-2,5-di-(tert-butylperoxy)hexyne-3 are preferred. The amount of organic peroxide to be blended is 0.01 parts by weight or more, preferably 0.1 parts by weight or more, more preferably 0.2 parts by weight or more, based on 100 parts by weight of the polyethylene resin, from the viewpoint of adhesiveness, and 5 parts by weight or less, preferably 4 parts by weight or less, more preferably 3 parts by weight or less, from the viewpoint of controlling the decrease in melt viscosity during acid modification. As the acid-modified polyethylene, commercially available products can be used, such as BYNEL and AMPLFY manufactured by Dow Chemical Company, Admer manufactured by Mitsui Chemicals, Inc., and Modic manufactured by Mitsubishi Chemical Corporation, and acid-modified high-density polyethylene, acid-modified low-density polyethylene, and acid-modified linear low-density polyethylene can be used alone or in combination of two or more types.
[0015] The MFR of the component (A) is preferably 0.1 to 15.0 g / 10 min. When the component (A) contains two or more acid-modified polyethylene resins, the MFR of each of the two or more acid-modified polyethylenes is preferably 0.1 to 15.0 g / 10 min, more preferably 13.0 g / 10 min or less, even more preferably 10.0 g / 10 min or less, and even more preferably 5.0 g / 10 min or less. In this specification, the MFR (melt flow rate) is a value measured according to the JIS K7210-1:2014 method under conditions of a test temperature of 190°C and a load of 2.16 kg. From the viewpoint of preventing blocking, the acid-modified polyethylene preferably has a melting point of 115° C. or more and 140° C. or less, more preferably 120° C. or more and 137° C. or less, and even more preferably 125° C. or more and 135° C. or less. In this specification, the melting point means a value measured by a differential scanning calorimeter (DSC). The density and MFR of acid-modified polyethylene are affected by the amount of acid modification and the type of acid modification, but the density is 0.91 to 0.97 g / cm 3 It is preferable to use a material with a density of 0.91 g / cm 3 If the density is less than 0.97g / cm3, the expected adhesive strength may not be obtained. 3 If the amount exceeds this range, it becomes difficult to obtain a resin that satisfies the MFR range of 0.1 to 15.0 g / 10 min.
[0016] (B) Linear low-density polyethylene In the thermoplastic adhesive film, linear low density polyethylene is an optional component. Linear low-density polyethylene (LLDPE) is a copolymer of ethylene and an α-olefin having 3 to 13 carbon atoms, and the side chains branched from the main chain of polymerized ethylene are shorter than those of low-density polyethylene (LDPE). By using linear low-density polyethylene, the strength of the thermoplastic adhesive film is improved, and the adhesive strength is improved. If high-density polyethylene or low-density polyethylene is used instead of linear low-density polyethylene, the strength of the thermoplastic adhesive film is likely to be reduced, and the adhesive strength may be weakened. As the linear low-density polyethylene, for example, Evolu manufactured by Prime Polymer Co., Ltd., Harmolex and Novatec manufactured by Japan Polyethylene Co., Ltd., Sumikasen L manufactured by Sumitomo Chemical Co., Ltd., Yumerit manufactured by Ube Maruzen Polyethylene Co., Ltd., etc. can be used, and one or more of these can be mixed and used.
[0017] The α-olefin is not particularly limited, but examples thereof include propylene, butene, pentene, methylpentene, hexene, octene, etc. Among these, at least one of 1-butene, 1-hexene, 1-octene, and 4-methyl-1-pentene is preferred from the viewpoint of the strength of the resulting thermoplastic adhesive film. Linear low-density polyethylene becomes a polymer with different shapes depending on the polymerization catalyst and polymerization method. As the linear low-density polyethylene used in the present invention, metallocene-catalyzed linear low-density polyethylene polymerized using a metallocene catalyst and Ziegler-Natta-catalyzed linear low-density polyethylene polymerized using a Ziegler-Natta catalyst can be used.
[0018] The MFR of component (B) is preferably 0.1 to 15.0 g / 10 min. When component (B) contains two or more types of linear low density polyethylene, the MFR of each of the two or more types of linear low density polyethylene is preferably 0.1 to 15.0 g / 10 min, more preferably 13.0 g / 10 min or less, even more preferably 10.0 g / 10 min or less, and even more preferably 5.0 g / 10 min or less. From the viewpoints of preventing blocking and low-temperature adhesion, the linear low-density polyethylene preferably has a melting point of 100° C. or more and 125° C. or less, and more preferably has a melting point of 110° C. or more and 120° C. or less. The linear low-density polyethylene has a density of 0.91 to 0.93 g / cm 3 It is preferable to use one of the following:
[0019] (C) Polyethylene elastomer Polyethylene elastomers have plastic and elastic properties, and are resins with greater flexibility than ordinary polyethylene resins. They are also sometimes written as very low density polyethylene (VLLDPE). Adding polyethylene elastomers gives flexibility to thermoplastic adhesive films, and contributes to improving peel adhesive strength in particular. Examples of polyethylene elastomers that can be used include Excellen manufactured by Sumitomo Chemical Co., Ltd., AFFINITY manufactured by Dow Chemical Co., Ltd., Kernel manufactured by Japan Polyethylene Co., Ltd., and Toughmer manufactured by Mitsui Chemicals Co., Ltd., and these can be used alone or in combination of two or more types.
[0020] The polyethylene elastomer is a copolymer of ethylene and an α-olefin. Examples of the α-olefin include propylene, butene, pentene, methylpentene, hexene, and octene. Among these, at least one of 1-butene, 1-hexene, 1-octene, and 4-methyl-1-pentene is preferred from the viewpoint of the adhesive strength of the resulting thermoplastic adhesive film. The polyethylene-based elastomer may further include diene units.
[0021] The MFR of component (C) is preferably 0.1 to 20.0 g / 10 min. When component (C) contains two or more polyethylene elastomers, the MFR of each of the two or more polyethylene elastomers is preferably 0.1 to 20.0 / 10 min, more preferably 15.0 g / 10 min or less, even more preferably 10.0 g / 10 min or less, and even more preferably 5.0 g / 10 min or less. The melting point of the polyethylene elastomer (C) is preferably lower than the melting point of the acid-modified polyethylene (A). When the polyethylene elastomer (C) contains linear very low density polyethylene, the melting point of the polyethylene elastomer (C) is preferably lower than the melting point of the linear very low density polyethylene (B). From the viewpoint of low-temperature adhesion, the melting point of the polyethylene elastomer (C) is preferably 50°C or higher and 120°C or lower, more preferably 55°C or higher and 110°C or lower. Polyethylene elastomers have a density of 0.85 to 0.91 g / cm 3 It is preferable to use one of the following:
[0022] The thermoplastic adhesive film used in the present invention contains 5 to 95% by weight of (A) and 5 to 95% by weight of (C) based on the entire resin composition (thermoplastic adhesive film). The weight ratio of (A) to (C) (A:C, total 100) is preferably 5 to 95:95 to 5, more preferably 20 to 80:80 to 20, and even more preferably 30 to 70:70 to 30. When the thermoplastic adhesive film used in the present invention contains (B) linear low density polyethylene, it is preferable that (B) is contained in an amount of 40% by weight or less based on the entire resin composition (thermoplastic adhesive film). The lower limit of the amount of the (B) component is not particularly limited, but it can be, for example, 0.1% by weight or more, 0.5% by weight or more, 1% by weight or more, 3% by weight or more, 5% by weight or more, etc. based on the entire resin composition. That is, in the thermoplastic adhesive film containing (B), the weight ratio of the (A) to (C) components, (A:B:C, where A+B+C=100), is preferably 5-95:0.1-40:95-5. This weight ratio is more preferably 10-90:1-35:90-10, and even more preferably 20-80:5-30:80-20. When the adherend has a particularly large value such as a coefficient of thermal expansion, a weight ratio of components (A) to (C) of 25-60:10-30:70-30 can ensure sufficient adhesive strength.
[0023] Furthermore, when the linear low density polyethylene (B) is contained, and the weight ratio (A:B:C) of the components (A) to (C) is expressed as α:β:γ (where α+β+γ=100), it is preferable that γ is equal to or greater than β, that is, the amount of the component (C) is equal to or greater than the amount of the component (B). If the amount of the component (B) is greater than the amount of the component (C), the thermoplastic adhesive film may become hard and the peel adhesive strength may decrease. γ is more preferably equal to or greater than β, more preferably equal to or greater than 3, and even more preferably equal to or greater than 5.
[0024] The MFR of the resin composition forming the thermoplastic adhesive film is preferably 0.1 to 20.0 g / 10 min. The MFR of the resin composition can be calculated as the sum of the MFR and weight ratio of each of the multiple resin components contained in the resin composition. For example, if the resin composition contains 20% by weight of a resin with an MFR of 1.0 g / 10 min, 40% by weight of a resin with an MFR of 2.0 g / 10 min, and 40% by weight of a resin with an MFR of 4.0 g / 10 min, the MFR of the resin composition is (1 x 0.2) + (2 x 0.4) + (4 x 0.4) = 2.6 g / 10 min. The thermoplastic adhesive film has a resin composition with an MFR of 0.1 to 20.0 g / 10 min, so that when the film is heated and melted to adhere, the molten thermoplastic adhesive film does not easily flow out between the adherends, and the adhesive shape does not easily collapse before solidification. If the MFR of the resin composition is less than 0.1 g / 10 min, the resulting thermoplastic adhesive film becomes hard, the wettability of the adhesive interface is poor, and the adhesive strength decreases. If the MFR of the resin composition is more than 20.0 g / 10 min, the strength of the thermoplastic adhesive film decreases, and the adhesive strength may decrease. Furthermore, when the film is heated and melted to adhere, the molten thermoplastic adhesive film may flow out between the adherends, and the adhesive shape may easily collapse before solidification.
[0025] The thermoplastic adhesive film is made of a resin composition containing the above-mentioned components (A) and (C) and optionally the component (B), but this resin composition may contain any materials other than the components (A) to (C), such as other thermoplastic resins, infrared absorbing materials, inorganic fillers, tackifiers, crosslinking agents, plasticizers, etc. However, the proportion of the total of the components (A) to (C) in the entire resin composition is preferably 90% by weight or more, more preferably 93% by weight or more, even more preferably 96% by weight or more, and even more preferably 97% by weight or more. The other thermoplastic resin can be used without any particular limitation as long as it can be uniformly kneaded with the (A) to (C) components, and examples thereof include high-density polyethylene, medium-density polyethylene, and low-density polyethylene. When the other thermoplastic resin is contained, its MFR is preferably 0.1 to 20.0 g / 10 min, more preferably 15.0 g / 10 min or less, even more preferably 10.0 g / 10 min or less, and even more preferably 5.0 g / 10 min or less. In addition, the MFR of the other thermoplastic resin is preferably included between the maximum and minimum values of the MFR of the (A) to (C) components, and the melting point of the other thermoplastic resin is preferably included between the maximum and minimum values of the melting points of the (A) to (C) components.
[0026] Examples of infrared absorbing materials include carbon black, graphene, graphite, diimonium salts, aminium salts, cyanine compounds, phthalocyanine compounds, dithiol metal complexes, naphthoquinone compounds, azo compounds, talc, etc. By containing a near-infrared absorbing material, it is possible to efficiently heat the material by irradiating it with infrared rays such as laser light, and adhesion becomes easy. Examples of inorganic fillers include talc, calcium carbonate, sepiolite, boehmite, bentonite, hydrotalcite, zeolite, silica, mica, quartz, titanium oxide, zinc oxide, glass beads, and metal fibers such as aluminum, nickel, and copper. By including an inorganic filler, the rigidity of the thermoplastic adhesive film can be increased.
[0027] The thermoplastic adhesive film can be obtained by known melt extrusion molding, and a film or sheet can be formed by melt extruding a resin composition from a T-die, circular die or the like, and then cooling and solidifying it. The thickness of the thermoplastic adhesive film is not particularly limited, but is preferably, for example, 10 to 500 μm. If the thickness of the film is less than 10 μm, the expected adhesive strength may not be obtained. On the other hand, if the thickness exceeds 500 μm, there is a risk that the film may protrude from between the adherends during thermal adhesion, or the tensile shear adhesive strength may be reduced due to the thickness of the film. In addition, the thermoplastic adhesive film used in the present invention may be subjected to a corona discharge treatment, a plasma discharge treatment, a UV / ozone treatment, a flame treatment, or the like on the surface in order to improve the surface wettability. The thickness of the film is more preferably 20 μm or more, more preferably 40 μm or more, more preferably 400 μm or less, and even more preferably 300 μm or less.
[0028] The thermoplastic adhesive film preferably has a tensile modulus of 50 MPa or more and 950 MPa or less, measured under the conditions of 23°C, 50% RH, 20 mm / min tensile speed, and 100 mm chuck distance, in accordance with JIS K7127. If the tensile modulus is less than 50 MPa, the strength of the thermoplastic adhesive film tends to be low, and the tensile shear adhesive strength and -30°C impact strength tend to be low. In addition, the thermoplastic adhesive film is soft, and tends to block easily. If the tensile modulus exceeds 950 MPa, the thermoplastic adhesive film tends to be hard, and the peel adhesive strength and -30°C impact strength tend to decrease. The thermoplastic adhesive film becomes an adhesive layer that adheres to an adherend while maintaining the film shape, and when the above-mentioned tensile elastic modulus is satisfied, the adhesive layer is not easily broken, and therefore can exhibit excellent adhesive strength. The tensile elastic modulus is preferably 100 MPa or more, more preferably 200 MPa or more, even more preferably 250 MPa or more, and more preferably 700 MPa or less, and even more preferably 400 MPa or less.
[0029] The thermoplastic adhesive film can be provided with a base layer on one side to form a multi-layer film or sheet. The base layer is used for the purpose of adjusting the thickness and physical properties such as bending strength, stiffness, and heat resistance of the thermoplastic adhesive film. The material is not particularly limited, but polyethylene resin, polyethylene terephthalate resin, polyamide resin, etc. can be used.
[0030] The thermoplastic adhesive film preferably has a -30°C impact strength of 2J or more, measured by the method described in the Examples below, after bonding the aluminum plate and ultra-high molecular weight polyethylene plate as the adherends. This -30°C impact strength is more preferably 2.2J or more, even more preferably 2.4J or more, even more preferably 2.6J or more, and even more preferably 2.7J or more. The thermoplastic adhesive film of the present invention is not likely to lose adhesive strength at low temperatures and is not likely to be broken even at low temperatures, so that breakage due to the adhesive film is unlikely to occur even in a low-temperature environment. When the adhesive strength at low temperatures is low, it is less than 2J.
[0031] The thermoplastic adhesive film preferably has a peel strength of 40N / 25mm or more, measured by the method described in the Examples below, after bonding the aluminum plate and ultra-high molecular weight polyethylene plate as the adherends. This peel strength is more preferably 60N / 25mm or more, more preferably 80N / 25mm or more, even more preferably 100N / 25mm or more, even more preferably 120N / 25mm or more, even more preferably 140N / 25mm or more, even more preferably 160N / 25mm or more, even more preferably 180N / 25mm or more, and even more preferably 200N / 25mm or more. If it is less than 40N / 25mm, peeling is likely to occur due to the difference in linear expansion coefficient when bonding different materials.
[0032] The thermoplastic adhesive film preferably has a tensile shear adhesive strength of 5 MPa or more, measured by the method described in the Examples below, after bonding the aluminum plate and ultra-high molecular weight polyethylene plate as adherends, more preferably 6 MPa or more, even more preferably 8 MPa or more, even more preferably 10 MPa or more, and even more preferably 13 MPa or more.
[0033] The thermoplastic adhesive film used in the present invention is used to bond two adherends to obtain an adherend, one of which is ultra-high molecular weight polyethylene (UHMWPE). The other adherend is not particularly limited as long as it can be adhered by the thermoplastic adhesive film used in the present invention, and can be made of any material such as resin, rubber, FRP (fiber reinforced plastic), wood, metal, paper, glass, pottery, ceramics, woven fabric, nonwoven fabric, etc. The thermoplastic adhesive film used in the present invention can be suitably used for bonding different materials such as UHMWPE and metal. The uses of the adhesive article of the present invention are not particularly limited, and it can be used as an adhesive material for producing adhesive articles for various uses, such as automobile interior parts, footwear such as shoes and sandals, furniture, housings for smartphones, tablet terminals and PCs, and housings for home appliances.
[0034] The conditions for the heat and pressure bonding of the thermoplastic adhesive film can be appropriately set according to the thickness of the thermoplastic adhesive film and the type of the adherend, but in the case of heat and pressure pressing, the set temperature of the hot plate is preferably 70 to 180° C. and the pressure is preferably 0.1 to 0.6 MPa. In addition to hot plate pressing, other heat and pressure bonding methods that can be used include high-frequency dielectric heating bonding, resistance heating bonding, high-frequency induction heating bonding, infrared heating bonding, laser heating bonding, autoclave heating bonding, heat lamination, ultrasonic heating bonding, vibration heating bonding, friction heating bonding, air hot pressing, pulse heating bonding, double belt press heating bonding, and insert molding heating bonding. In the bonded body of the present invention, at least one of the adherends is a thermoplastic resin, ultra-high molecular weight polyethylene. The bonding temperature, which is the heating temperature during bonding to obtain the bonded body of the present invention, is set to (the melting point of the thermoplastic resin that is the adherend)>(bonding temperature)≧(melting point of the acid-modified polyethylene resin)-5°C (wherein the melting point is a value measured by a differential scanning calorimeter), whereby the deformation of the adherends can be suppressed and the bonded bodies can be bonded. The thermoplastic adhesive film contains a polyethylene resin with a low melting point, and therefore, compared to a thermoplastic adhesive film mainly composed of a polypropylene resin, the thermoplastic adhesive film can bond at a low temperature, for example, at 125°C to 135°C, and can bond ultra-high molecular weight polyethylene, which has a lower melting point than polypropylene, without deformation. EXAMPLES
[0035] The present invention will now be described in more detail with reference to examples. It should be noted that the examples show one embodiment of the present invention, and the present invention is not limited thereto.
[0036] The resins used in the present invention and their physical properties are shown in Table 1. [Table 1]
[0037] The components were mixed so as to obtain the composition shown in Table 2, melt-kneaded, and molded into a film having a thickness of 80 μm to obtain each thermoplastic adhesive film.
[0038] The thermoplastic adhesive film thus obtained was subjected to the following evaluations, and the results are shown in Table 2. <Tensile modulus> From the obtained film, a test piece type 2 (width 15 mm) was prepared in accordance with JIS K7127. The tensile modulus (MPa) was measured using an autograph (Shimadzu Corporation AGS-X) under conditions of 23°C, 50% RH, a tensile speed of 20 mm / min, and a chuck distance of 100 mm, in accordance with JIS K7127. The tensile modulus was measured only in the MD direction of the film.
[0039] <-30℃ impact strength> With reference to JIS K6854-3, the thermoplastic adhesive films (0.08 mm thick x 12.5 mm wide x 10 mm long) of Examples 1 to 16 and Comparative Examples 1 to 4 were layered between an aluminum plate (0.5 mm thick x 12.5 mm wide x 130 mm long) and an ultra-high molecular weight polyethylene plate (0.5 mm thick x 12.5 mm wide x 130 mm long) at a length of 10 mm to form a three-layer structure. Using a hot plate press (CYPT-50 manufactured by Shinto Kogyo) set at 180°C on the aluminum plate side and 70°C on the ultra-high molecular weight polyethylene side, the films were heat-pressurized and bonded at 0.5 MPa for 60 seconds to obtain bonded samples. The non-bonded ends of the upper and lower adherends were bent 90 degrees to form a T-shape, and each end was fixed so that the bonded portion was in the center of the test piece clamp of a film impact tester (TM-701-200, manufactured by Tester Sangyo), and left to stand for 5 minutes in an environment of -30°C. Then, an impact was applied to the ultra-high molecular weight PE surface near the bonded surface by free-fall using a pendulum with a 1 / 2 inch ball at the tip, and the strength was measured when the bonded portion broke or the interface peeled off at the bonded portion, and the -30°C impact strength (J) was obtained.
[0040] <Peel adhesive strength> With reference to JIS K6854-3, the thermoplastic adhesive films (0.08 mm thick x 25 mm wide x 100 mm long) of Examples 1 to 16 and Comparative Examples 1 to 4 were layered between an aluminum plate (0.5 mm thick x 25 mm wide x 130 mm long) and an ultra-high molecular weight polyethylene plate (0.5 mm thick x 25 mm wide x 130 mm long) at a length of 100 mm to form a three-layer structure. Using a hot plate press (CYPT-50 manufactured by Shinto Kogyo) set at 180°C on the aluminum plate side and 70°C on the ultra-high molecular weight polyethylene side, the films were heat-pressurized and bonded at 0.6 MPa for 60 seconds to obtain bonded samples. The non-bonded ends of the upper and lower adherends were bent 90 degrees to form a T-shape, and the ends were gripped with a jig up to 20 mm from the T-shape. The lower adherend was fixed, and the jig gripping the upper adherend was pulled upward at a tensile speed of 100 mm / min. The strength at which the bonded area broke or the interface peeled off at the bonded area was measured with an autograph (Shimadzu Corporation AGS-X) to obtain the peel adhesion strength (N / 25 mm).
[0041] <Tensile shear adhesive strength> With reference to JIS K6850, the thermoplastic adhesive films (0.08 mm thick x 20 mm wide x 10 mm long) of Examples 1 to 16 and Comparative Examples 1 to 4 were layered between an iron plate (0.8 mm thick x 20 mm wide x 75 mm long) and an ultra-high molecular weight polyethylene plate (5 mm thick x 20 mm wide x 75 mm long) at a length of 10 mm to form a three-layer structure. This was then thermally and pressurized and bonded at 0.5 MPa for 60 seconds using a hot plate press (CYPT-50 manufactured by Shinto Kogyo) set at 180°C on the iron plate side and 70°C on the ultra-high molecular weight polyethylene side to obtain an adhesive sample. The non-bonded ends of the upper and lower adherends were gripped with a jig up to a point 50 mm from the end. The jig gripping the upper and lower adherends was pulled upward at a tensile speed of 100 mm / min. The strength when the bonded area broke or the interface peeled off at the bonded area was measured with an autograph (Shimadzu Corporation AGS-X), and the tensile shear adhesive strength (MPa) was obtained by dividing this by the bonded area.
[0042] [Table 2]
[0043] The bonded bodies using the thermoplastic adhesive films obtained in Examples 1 to 16 of the present invention had a large impact strength of 2 J or more at -30°C, and were excellent in adhesion at low temperatures. In addition, the bonded bodies obtained in Examples 1 to 16 of the present invention were excellent in both peel adhesion strength and tensile shear adhesion strength, and showed sufficient adhesion to ultra-high molecular weight polyethylene.
Claims
1. The resin composition comprises (A) an acid-modified polyethylene and (C) a polyethylene-based elastomer, an adherend is adhered to both sides of a thermoplastic adhesive film containing 5 to 95% by weight of (A) and 5 to 95% by weight of (C) based on the entire resin composition; An adhesive structure, characterized in that at least one of the adherends is ultra-high molecular weight polyethylene.
2. The thermoplastic adhesive film contains (B) a linear low-density polyethylene, 2. The adhesive body according to claim 1, wherein the resin composition contains 40% by weight or less of the (B) based on the entire resin composition.
3. The thermoplastic adhesive film has a tensile modulus of 50 MPa or more and 950 MPa or less, 3. The adhesive body according to claim 1, wherein the film thickness is from 10 μm to 500 μm.
4. 3. The bonded structure according to claim 1, wherein the −30° C. impact strength measured by the following method is 2 J or more. (Method for measuring impact strength at -30°C) With reference to JIS K6854-3, a thermoplastic adhesive film (0.08 mm thick x 12.5 mm wide x 10 mm long) was layered between an aluminum plate (0.5 mm thick x 12.5 mm wide x 130 mm long) and an ultra-high molecular weight polyethylene plate (0.5 mm thick x 12.5 mm wide x 130 mm long) at a length of 10 mm to form a three-layer structure. The aluminum plate side was set to 180°C and the ultra-high molecular weight polyethylene side was set to 70°C. Using a hot plate press (CYPT-50 manufactured by Shinto Kogyo Co., Ltd.), the aluminum plate side was set to 180°C and the ultra-high molecular weight polyethylene side was set to 70°C. The plate was then heat-pressurized and bonded at 0.5 MPa for 60 seconds to obtain an adhesive sample. The non-bonded ends of the upper and lower adherends were bent 90 degrees to form a T-shape, and each end was fixed so that the bonded portion was at the center of the test piece clamp of a film impact tester (TM-701-200 manufactured by Tester Sangyo), and the specimen was allowed to stand for 5 minutes in an environment at -30°C. Thereafter, an impact was applied to the ultra-high molecular weight polyethylene surface near the bonded surface by free fall using a pendulum with a 1 / 2 inch ball at the tip, and the strength was measured when the bonded portion broke or the interface peeled off at the bonded portion, and the -30°C impact strength (J) was obtained.
5. 3. The adhesive structure according to claim 1, wherein the peel adhesion strength measured by the following method is 40 N / 25 mm or more. (Method of measuring peel adhesive strength) With reference to JIS K6854-3, a thermoplastic adhesive film (0.08 mm thick x 25 mm wide x 100 mm long) was layered between an aluminum plate (0.5 mm thick x 25 mm wide x 130 mm long) and an ultra-high molecular weight polyethylene plate (0.5 mm thick x 25 mm wide x 130 mm long), arranged at a length of 100 mm to form a three-layer structure, and a hot plate press (CYPT-50 manufactured by Shinto Kogyo Co., Ltd.) set at 180°C on the aluminum plate side and 70°C on the ultra-high molecular weight polyethylene side was used to perform hot press bonding under conditions of 0.6 MPa and 60 seconds to obtain an adhesion sample. The ends of the upper and lower adherends that were not bonded to each other were bent 90 degrees to form a T-shape, and the ends were gripped by a jig up to a point 20 mm from the T-shape. The lower adherend was fixed, and the jig gripping the upper adherend was pulled upward at a tensile speed of 100 mm / min. The strength when the bonded portion broke or the interface peeled off at the bonded portion was measured using an autograph (AGS-X, manufactured by Shimadzu Corporation) to obtain the peel adhesive strength (N / 25 mm).
6. 3. The adhesive structure according to claim 1, wherein the tensile shear adhesive strength measured by the following method is 5 MPa or more. (Method of measuring tensile shear adhesive strength) With reference to JIS K6850, a thermoplastic adhesive film (0.08 mm thick x 20 mm wide x 10 mm long) was layered between an iron plate (0.8 mm thick x 20 mm wide x 75 mm long) and an ultra-high molecular weight polyethylene plate (5 mm thick x 20 mm wide x 75 mm long) at a length of 10 mm to form a three-layer structure, which was then heat-pressurized and bonded at 0.5 MPa for 60 seconds using a hot plate press (CYPT-50 manufactured by Shinto Kogyo Co., Ltd.) set at 180°C on the iron plate side and 70°C on the ultra-high molecular weight polyethylene side to obtain an adhesion sample. The unbonded ends of the upper and lower adherends were gripped with a jig up to a point 50 mm from the end. The lower adherend was fixed, and the jig gripping the upper adherend was pulled upward at a pulling speed of 100 mm / min. The strength when the bonded portion broke or the interface peeled off at the bonded portion was measured using an autograph (AGS-X, manufactured by Shimadzu Corporation), and the measured strength was divided by the bonded area to obtain the tensile shear adhesive strength (MPa).
7. 3. The adhesive structure according to claim 1, wherein the other adherend is a metal.
Citation Information
Patent Citations
EVA (ethylene vinyl acetate) hot melt glue for UHMWPE (ultra high molecular weight polyethylene) product adhesion and preparation method thereof
CN108047998A
Laminate consisting of ultra-high-molecular-weight polyethylene
JP1986143137A
laminate
JP1991205151A
Composite bulletproof laminate
JP2018507123A
Thermoplastic adhesive film
JP2023157869A